Syntheses, structures and magnetic properties of macrocyclic Schiff base-supported homodinuclear lanthanide complexes. Issue 33 (13th August 2018) - Gao, Feng; Zhang, Yi-Quan; Sun, Wang; Liu, Huan; Chen, Xiaoyu
Abstract : Five macrocyclic Schiff base-supported homodinuclear lanthanide complexes were successfully designed and synthesized by template strategy. Theoretical analysis and magnetic measurements reveal dysprosium complex1 behaves as a typical SMM with intramolecular ferromagnetic Dy 3+ ⋯Dy 3+ interaction. Abstract : Five new homodinuclear lanthanide complexes with the general formula [(acac)4 Ln2 (L)] (Ln 3+ = Dy 3+ (1 ), Tb 3+ (2 ), Ho 3+ (3 ), Er 3+ (4 ), and Gd (5 )) were synthesized by one-pot [2 + 2] condensation of 2, 6-diformyl-4-methylphenol and 1, 3-diaminopropane in the presence of various lanthanide acetylacetonates. The eight-coordinate Ln(iii ) centre adopts a slightly distorted square antiprism geometry with D 4d symmetry. Theoretical analysis and magnetic measurements reveal that the corresponding Dy complex1 exhibits slow magnetic relaxation behavior, characteristic of a typical SMM with the intramolecular ferromagnetic Dy 3+ ⋯Dy 3+ interaction.